Recent advances in hydrogels-based osteosarcoma therapy - Tian, Hao; Wu, Ronghui; Feng, Na; Zhang, Jinrui; Zuo, Jianlin (Frontiers in Bioengineering and Biotechnology, 2022)
Osteosarcoma (OS), as a typical kind of bone tumors, has a high incidence among adolescents. Traditional tumor eradication avenues for OS such as chemotherapy, surgical therapy and radiation therapy usually have their own drawbacks including recurrence and metastasis. In addition, another serious issue in the treatment of OS is bone repair because the bone after tumor invasion usually has difficulty in repairing itself. Hydrogels, as a synthetic or natural platform with a porous three-dimensional structure, can be applied as desirable platforms for OS treatment. They can not only be used as carriers for tumor therapeutic drugs but mimic the extracellular matrix for the growth and differentiation of mesenchymal stem cells (MSCs), thus providing tumor treatment and enhancing bone regeneration at the same time. This review focuses the application of hydrogels in OS suppression and bone regeneration, and give some suggests on future development.